2016
DOI: 10.1158/1940-6207.capr-15-0417
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein Isolate Protects Against Ethanol-Mediated Tumor Progression in Diethylnitrosamine-Treated Male Mice

Abstract: In this study, diethylnitrosamine-treated male mice were assigned to 3 groups: a 35% high fat ethanol liquid diet (EtOH) with casein as the protein source, the same EtOH liquid diet with soy protein isolate as the sole protein source (EtOH/SPI) and a chow group. EtOH feeding continued for 16 wks. As expected, EtOH increased the incidence and multiplicity of basophilic lesions and adenomas compared to the chow group, p<0.05. Soy protein replacement of casein in the EtOH diet significantly reduced adenoma progre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…SPI is not purely a protein preparation, as it also contains more than a 100 different phytochemicals including flavonoids. 10,16 Consistent with our findings, several phytochemicals are known to enter the circulation allowing them to exert physiological effects at the wholebody level. Since soy flavonoids have structural similarities to estrogen, they have been termed phytoestrogens.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…SPI is not purely a protein preparation, as it also contains more than a 100 different phytochemicals including flavonoids. 10,16 Consistent with our findings, several phytochemicals are known to enter the circulation allowing them to exert physiological effects at the wholebody level. Since soy flavonoids have structural similarities to estrogen, they have been termed phytoestrogens.…”
Section: Discussionsupporting
confidence: 91%
“…Support for this protective effect comes from a wealth of epidemiological and experimental animal studies associating soy protein or soy-derived phytochemicals with anti-cancer properties, including anti-proliferative effects associated with reduced Wnt/b-catenin signaling. 10,30,31 In this study, using PCR arrays, we observed an overall induction of Wnt/b-catenin pathway genes for HF liquid diets compared to chow (Supplementary Table 2 and Figure 5). Interestingly, the effects of SPI on Wnt/b-catenin signaling were found to be stimulatory rather than inhibitory.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Liver (∼100 mg) and feces (∼50 mg) lipids were extracted by chloroform:isopropanol:NP-40 (7:11:0.1), and total, free, and esterified cholesterol concentrations were measured by using a commercially available assay (ab65359; Abcam). Nuclear and membrane protein fractions were obtained as previously described (29). Proteins (30 μg) were separated by SDS-PAGE by standard methods.…”
Section: Serum Biochemistry After Being Killed Blood Was Collectedmentioning
confidence: 99%